Laser shock peening for microstructure tailoring of additive manufactured Inconel 718 parts - Heng, Zi Yun (Nanyang Technological University, 2020)
Inconel 718 alloy is used extensively in the aviation field. Numerous types of additive manufacturing for metallic parts are available in the market currently. In this project, it focuses on material produced by Selective Laser Melting (SLM). SLM metallic parts are recognized for their diverse microstructures. Laser Shock Peening (LSP) was done in this study on an SLM manufactured Inconel 718 component. The LSP treatment targets to reduce the amount of porosity in the material. When annealed for a short period of time, samples became significantly softer, and grain refinement is expected in areas affected by LSP treatment. Recrystallisation is anticipated for LSP samples to transform into equiaxed structure. Therefore, the LSP approach provides an innovative route to selectively control microstructures and mechanical properties of SLM components. Future research can be executed by considering more mechanical properties in selecting the most effective scenario to make the analysis more realistic. Chapter 1 of this report has presented the background of the material, the objective and scope of this project. In chapter 2, more information on the material, as well as the experiments on various processes will be discussed in detail. In chapter 3, the methodology will be presented. In chapter 4, the results of the experiment will be discussed. Lastly, the final chapters will conclude and highlight areas to be improved for future projects.